PENGARUH PEER LEADER SUPPORT TERHADAP KEPATUHAN MINUM OBAT ORANG DENGAN HIV AIDS - Gede Arya Bagus Arisudhana; Ni Putu Dita Wulandari; Nyoman Eta Risnawati; Desak Putu Cristine Monica (Fakultas Keperawatan, Universitas Riau, 2022)
Adherence to taking medication was so important to suppress HIV suppression. Maintaining compliance can be done using a peer support intervention approach. The purpose of this study was to determine the effect of peer leader support on medication adherence of people living with HIV/AIDS. The research method used is one group pre-test post-test. The sample in this study was determined using a consecutive technique, with a total sample of 25 respondents. The Antiretroviral Adherence Scale was used to measure the adherence level. The peer leader support treatment procedure was based on empowerment, self-management, experience exploration, motivation, and problem-solving in a systematic way and administered for 14 weeks. The data analysis used paired t-test. The results showed that there was an increase in the average value of adherence before being given the intervention (3.04) and after being given the intervention (4.40). The bivariate analysis result obtained p-value < 0.000 (α = 0.05). Based on the value of p<α, the peer leader support was affected adherence to taking medication in PLWHA. It is necessary to conduct a peer intervention model to explore changes in viral load and CD4 cell values associated with ARV adherence